O PRIVIRE BIBLICĂ ASUPRA VIEŢII LUI IOSIF, CA MODEL DE INTEGRITATE ŞI DE CONŞTIINŢĂ ÎN EGIPTUL ANTIC (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
A Biblical View over Joseph’s Life, as a Model of Integrity and ConsciousnessJoseph is one of the personalities in the book of Genesis, and he occupies most of the space in its economy. Even though his descendency was enviable – Jacob’s son, Isaac’s grandson and Abraham’s great-grandson – he didn’t have an easy life.This study presents Joseph’s life, according to scriptural accounts, from his paternal home to the Royal Palace of Egypt. During all his life, wherever God put him, Joseph proved integrity, keeping his conscious clean in all the situations he had to deal with.